Fotografía N°4 - Octava entrega de armas en Nunchía, Casanare, 1953 (1953)
Los cabecillas entregados en Nunchía; Luis Eduardo Arenas, Víctor Agudelo, Berardo Giraldo, Francisco Giraldo, José Pan, Luis Cárdenas y Marco Achagua.